Out of Africa: what can we learn from HIV-2 about protective immunity to HIV-1? - Rowland-Jones, S; Whittle, H (2007)
Most people infected with human immunodeficiency virus 2 (HIV-2) do not progress to disease, even though the minority who do cannot be distinguished clinically from HIV-1-infected patients. Here we review what is known about the basis of viral control in HIV-2 infection.